Predictors of stunting with particular focus on complementary feeding practices: A cross-sectional study in the Northern Province of Rwanda - Uwiringiyimana, V. (2020)
There was a 42% stunting prevalence. Prevalence of continued breastfeeding and exclusive breastfeeding were 92% and 50%, respectively. Most children (62%) fell into the low dietary diversity score group. The nutrient intake from complementary foods was below recommendations. The odds of stunting were higher in children >12 mo of age (odds ratio [OR], 1.18; 95% confidence interval [CI], 1.08–1.29). Exclusive breastfeeding (OR, 0.22; 95% CI, 0.10–0.48) and deworming tablet use in the previous 6 mo (OR, 0.25; 95% CI, 0.07–0.80) decreased significantly the odds of stunting in children. Also, the body mass index of the caretaker (β = 0.08 kg/m2; 95% CI, 0.00–0.17) and dietary zinc intake (β = 1.89 mg/d; 95% CI, 0.29–3.49) were positively associated with the height-for-age z scores.